Recent advances in biosynthesis of non-canonical amino acids and their potentials in strain engineering - Zhen Hou; Junkai Tuo; Xiaoyan Ma; Yi-Xin Huo (Results in Engineering)
Non-canonical amino acids (ncAAs), as derivatives of canonical amino acids (cAAs), when specifically incorporated into proteins, could enrich protein functions. Currently, ncAAs mostly depend on chemical synthesis; however, biosynthesis of ncAAs could solve the problems of low transmembrane transport efficiency and potential toxicity of exogenously added ncAAs. Moreover, the biosynthesis of ncAAs is eco-friendly and economical. In this article, we firstly reviewed recent advances in the biosynthesis strategies of ncAAs, including hijacking the biosynthesis pathways of cAAs, deriving ncAAs from cAAs, and de novo biosynthesis of ncAAs, from the advantages, shortcomings, and potentials of these three strategies. Secondly, we discussed the applications of ncAAs in bacterial-based therapeutics, whole-cell biocatalysts, and biosafety. Finally, we provide guidance for the improvement of ncAAs biosynthesis and put forward perspectives on applying ncAAs in strain engineering. This work will promote the in situ synthesis of ncAAs modified proteins and unleash the potentials of ncAAs in strain engineering.